The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2495/hpsm140101
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization of polymer composite cement systems

Abstract: The early hydration behaviour of two different polymer composites cement systems (PCCS) that hypothetically affects efflorescence has been investigated through physicochemical characterization namely Puddle Test (PT), Standard Chemical Method (SCM), Compressive Strength Test (CS), X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). PCCS mortar samples were prepared with water-to-cement ratio (w/c) of 0.50. Commercially available polymer additives namely Styrene Butadiene Rubber (SBR) and Styrene Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…NS particles act as nucleation sites to accelerate the hydration [26]. Due to high surface area and spherical shape, NS can enhance performance of cementbased material due to pozzolanic reaction of silica with calcium hydroxide, CH to form additional calcium silicate hydrate, C-S-H which represent the strength of cement-based product [27].As the most widely investigated of nano material in cement and concrete research, NS was found to be effective in enhancing the hydration process [28], the mechanical properties [29], and the durability [30] of cement-based material to a great extent.…”
Section: Pozzolanic Reactions and Pore Filling Effect Of Sfcc And Ns mentioning
confidence: 99%
“…NS particles act as nucleation sites to accelerate the hydration [26]. Due to high surface area and spherical shape, NS can enhance performance of cementbased material due to pozzolanic reaction of silica with calcium hydroxide, CH to form additional calcium silicate hydrate, C-S-H which represent the strength of cement-based product [27].As the most widely investigated of nano material in cement and concrete research, NS was found to be effective in enhancing the hydration process [28], the mechanical properties [29], and the durability [30] of cement-based material to a great extent.…”
Section: Pozzolanic Reactions and Pore Filling Effect Of Sfcc And Ns mentioning
confidence: 99%